A COMPARATIVE STUDY OF TENELIGLIPTIN VERSUS HYDROXYCHLOROQUINE AS ADD ON THERAPY IN UNCONTROLLED TYPE-II DIABETES MELLITUS PATIENTS - KRUNAL NATVARLAL CHAUHAN,; ALKA YADAV,; ANURAG JAIN,; VIPIN KUMAR,; RAHUL KUMAR PAL,; JITENDRA KUMAR DONERIA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aimed to compare the efficacy and safety of teneligliptin versus hydroxychloroquine (HCQ) as add-on therapy in uncontrolled T2DM patients. To measure the safety and efficacy of Teneligliptin and Hydroxychloroquine as add on therapy in uncontrolled type-2 diabetes mellitus patients. To compare the safety and efficacy of Teneligliptin and Hydroxychloroquine during the study. To assess the Glycaemic control in patients of Type-2 diabetes mellitus before treatment and after treatment. Methods: This randomized, Observational and Prospective study enrolled 124 uncontrolled T2DM patients who were inadequately controlled on Metformin and Glimepiride therapy. Patients were randomly assigned to receive either teneligliptin (20mg/day) or HCQ (400mg/d ay) as add-on therapy for week 4,12 and 24 weeks. The primary outcome was the change in HbA1c from baseline to week 24. Results: Both Teneligliptin and HCQ significantly reduced HbA1c levels from baseline, with a greater reduction observed in the Teneligliptin group (p < 0.001). Additionally, the Teneligliptin group demonstrated improved fasting blood sugar (FBS) and postprandial glucose (PPG) levels in comparison to Hydroxychloroquine. Conclusion: This study suggests that Teneligliptin is a more effective and tolerable add-on therapy compared to Hydroxychloroquine in uncontrolled T2DM patients, highlighting its potential as a valuable treatment option for improving glycaemic control.